Protective effects and potential mechanisms of fermented egg-milk peptides on the damaged intestinal barrier - Lyu, Siwen; Yang, Qi; Duan, Xuehui; Liu, Xuanting; Du, Zhiyang; Shang, Xiaomin; Xu, Menglei; Liu, Jingbo; Pan, Fengguang; Zhang, Ting (Frontiers in Nutrition, 2022)
Fermented egg-milk peptides (FEMPs) could enhance the colon intestinal barrier and upgrade the expression of zonula occludens-1 and mucin 2. Besides, the underlying biological mechanism and the targets FEMPs could regulate are analyzed in our study. Herein, the immunofluorescence technique and western blot were utilized to evaluate the repair of the intestinal barrier. Network pharmacology analysis and bioinformatics methods were performed to investigate the targets and pathways affected by FEMPs. The animal experiments showed that FEMPs could restore the intestinal damage and enhance the expression of two key proteins. The pharmacological results revealed that FEMPs could regulate the targets related to kinase activity, such as AKT, CASP, RAF, and GSK, and the above targets could produce co-interaction with each other. GO analysis indicated that the targets regulated by FEMPs could participate in the kinase activity metabolic process. KEGG enrichment revealed that the core targets were enriched in the pathways related to cell apoptosis and other important procedures. Molecular docking demonstrated that FEMPs could bind with the key target AKT via hydrogen bonds and salt bridges interactions. Our study combines the experiment in vivo with the method in silico and investigates the interaction between peptides and targets in a pattern of multi-targets and multi-pathway, which could offer a new perspective to the functional validation and potential application of bioactive peptides.